ESTABLISHMENT AND ASSISTANCE OF INDEPENDENT CARE FOR THE USE OF FAMILY MEDICINAL PLANTS FOR SOCIETY - Kurniawan, K; Istiqomah, Solikah Ana; Budi Sawitri, Satwika (Jurnal Abdimas Kesehatan (JAKes), 2023)
Health Effort Based Human Resources is a real fact of community participated in health development that can trigger the community empowerment activities, such as Family Medicinal Plants (FMP). FMP are several kinds of selection plants that could be planted in the yard or home environment. The existence of this plants in the home yard are important, especially for the family with lack of access to the health services. This was a community service; community empowerment entitled “Establishment and Assistance for Independent Care for the Use of Family Medicinal Plants (TOGA) in the Community" in Tempursari Hamlet, Karanganyar, Sambungmacan, Sragen Regency. The aims were to improve the community and cadre knowledge and ability about the utization of FMP. There were 16 people involved in this community service. The instruments were pre-posttest questionnaire and observation cheklist. The analize was used frequency distribution, graph for the pre-posttest value, and also give a module about the Family Medicinal Plants (FMP) and 5 kinds of medicinal plants to the participants. The result showed mean of pretest was 71,56 and its increase to 84,69 in posttest, it showed the achievement of the Communication Information and Education (CIE)implementation and the dissemination that the minimum score level of posttest was 75. It means, there were the raising level of community knowledge about FMP and the utilization. It is recommended to the public health center to held the workshop and founding the cadre and community about FMP and the utilization